ANALISIS KINERJA SISTEM KELISTRIKAN UNIVERSITAS LANCANG KUNING - Abrar Tanjung (UIN Sultan Syarif Kasim Riau, 2015)
To distribute the electrical power needs of electricity producers to consumers required a distribution network and substations. Based on General Requirements for Electrical Installations ( PUIL ) 2000 and Standard State Electricity Company ( SPLN ), the system can be said to be effective if the voltage drop does not exceed 5 % of the nominal voltage and power loss does not exceed 10 % of the total power supplied The electrical system at the University of Lancang Kuning need to pay attention to large cross-section conductor and conductor prisoners are used to minimize power loss and voltage drop. The reliability of the electrical power distribution system is determined by efforts to minimize power loss and voltage drop occurs in the electrical system. Power loss and voltage drop affects the power distribution capabilities, both of which result from pengahantar channel length between the transformer with the buildings as user load, interference with electrical systems. This study aimed to analyze the voltage drop calculation, over load and power losses and balance the load on the Lancang Kuning University.Results of analysis and calculation of electrical systems Lancang Kuning University gained power loss total of 23.5 kW and low voltage three phase occurred in the law school of 237, 5 volts and load imbalance of the phase R = 199.15 Amper ; Amper phase S = 154.05; and phase T = 121.6 AmperKeywords: electrical system, power losses, voltage drop